Numerical analysis of the dynamics of a curvilinear pipeline - Tkachenko, Oleg Pavlovich (Computational Continuum Mechanics, 2012)
Numerical experiments on the mechanics of the slow motion of a pipeline are designed. It is established that the considered mathematical model adequately describes the known phenomena of the dynamics of extended pipes and can be extended to the case of variable internal pressure drop. Calculations have shown that the cross-sections of the extended curvilinear thin-walled pipeline experience deplanation, which has been confirmed experimentally.